Hyperglycemia exacerbates ischemic stroke outcome independent of platelet glucose uptake. (27th November 2020) - Denorme, Frederik; Portier, Irina; Kosaka, Yasuhiro; Campbell, Robert A.
Abstract: Objective: Hyperglycemia is a common comorbidity for ischemic stroke and is associated with worsened neurological outcomes. Platelets are central mediators of ischemic stroke and hyperglycemia mediates platelet hyperactivity. In this study, we investigated the contribution of platelet glucose metabolism to ischemic stroke. Methods: Mice lacking both Glut1 and Glut3 specifically in platelets (DKO) and their littermate controls (WT) were subjected to 1‐hour transient middle cerebral artery occlusion under normoglycemic and streptozotocin‐induced hyperglycemic conditions after which stroke outcomes, platelet activation, and platelet‐neutrophil aggregate (PNA) formation were examined. Results: Under normoglycemic conditions, DKO mice were protected from ischemic stroke with smaller brain infarct volumes and improved cerebral blood flow. In addition, DKO mice had reduced platelet activation, PNA, and cerebral neutrophil recruitment after stroke. Hyperglycemia significantly increased infarct size and cerebral Evans blue extravasation and worsened neurological outcomes and cerebral blood flow in both WT and DKO mice, abolishing the protective effect witnessed under normoglycemic conditions. Flow cytometric analysis after stroke demonstrated increased platelet activation and neutrophil trafficking to the brain, independent of platelet glucose metabolism. Finally, platelets from healthy DKO mice were unable to become procoagulant upon dual agonist stimulation. Conversely, hyperglycemia increased platelet mitochondrial reactive oxygen species production which potentiated procoagulant platelet formation in WT mice and restored procoagulant platelet formation in DKO mice. Conclusion: Hyperglycemia aggravates ischemic stroke outcome independent of platelet glucose uptake. Furthermore, we demonstrated that hyperglycemia primes procoagulant platelet formation. This underlines the therapeutic potential for strategies targeting procoagulant platelet formation for the treatment of acute ischemic stroke.